Assessing the potential of steel as a substrate for building integrated photovoltaic applications. (1st November 2018) - Hughes, Laurie; Bristow, Noel; Korochkina, Tatyana; Sanchez, Pascal; Gomez, David; Kettle, Jeff; Gethin, David
Highlights: Industrial viability of steel substrates for BIPV at production scale analysed. State of the art review of the suitability of steel considered. Review of competing technologies given. Methodical approach for manufacturing cost model for BIPVs. Abstract: Government edicts and national time bound policy directives are shaping the drive toward cost effective renewables such as photovoltaics (PV). Building Integrated Photovoltaics (BIPV) has the potential to provide significant energy generation by utilising the existing building infrastructure as a power generator, engendering a transformation shift from traditional energy sources. This research presents an innovative study on the industrial viability of utilising "rough" low carbon steel integrated with an Intermediate Layer (IL) to develop lower cost thin film BIPV products and is compared to existing commercial products. Consideration of the final product cost is given and potential business models to enter the BIPV are identified. The lab scale and upscaling elements of the research support the significant benefits of an approach that extends beyond the use of expensive solar grade steel. A state-of-the-art review of existing steel-based BIPV products is given and used as a benchmark to compare the new products. The results demonstrate that a competitively commercial product is viable and also highlight the strong potential for the adoption of a "rough" steel + IL focused approach to BIPV manufacture and a potential new direction to develop cost efficiencies in an increasingly competitive market.